2009
DOI: 10.4156/jdcta.vol3.issue3.22
|View full text |Cite
|
Sign up to set email alerts
|

On the Security Issues in Wireless Body Area Networks

Abstract: The emerging Wireless Body Area Networks (WBANs) have great potential to revolutionize the future of ubiquitous health technologies. They provide unprecedented opportunities to monitor the patient's health status with real-time updates to the physician. Since WBAN devices are used to collect sensitive (lifecritical) information and may operate in hostile environments, they require strict security mechanisms to prevent the malicious interaction with the system. However, unlike Wireless Sensor Network (WSN) devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 3 publications
(4 reference statements)
0
60
0
Order By: Relevance
“…Spoofing Attack: where the attacker targets the routing information to perform several disruptions such as spoofing, 230 | P a g e www.ijacsa.thesai.org altering, or replay the routing information, leading to complicate the network by creating routing loops [9].…”
Section: ) Attacks At Data Collection Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Spoofing Attack: where the attacker targets the routing information to perform several disruptions such as spoofing, 230 | P a g e www.ijacsa.thesai.org altering, or replay the routing information, leading to complicate the network by creating routing loops [9].…”
Section: ) Attacks At Data Collection Levelmentioning
confidence: 99%
“…Specifically, threats were emerged at each level of the system, for instance: At data collection level [5][6][7][8][9][10], At transmission level [11][12][13][14], and At storage level [15][16][17][18][19]. These threats were described in Section III.…”
Section: Introductionmentioning
confidence: 99%
“…In case of medical applications, the security threats may lead a patient to a dangerous condition, and sometimes to the death of the patient [4]. WBAN communication can…”
Section: Introductionmentioning
confidence: 99%
“…Some work has also been proposed for healthcare applications using WSNs [14][15][16][17]. In 2012, Kumar et al [18] observed that most of the schemes proposed for WSNs such as [9,10,12,13] fall short to provide security and also require heavy computational load and high communication cost.…”
Section: Introductionmentioning
confidence: 99%